HUBUNGAN KECERDASAN EMOSIONAL DENGAN KETERAMPILAN MENGELOLA KELAS GURU PAUD DI KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Syahidah '; Zulkifli N; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract:This study has to determine the relationship of emotional intelligenceand classroom management skills kindergarten teacher in the Kateman district IndragiriHilir regency. Population in this study is a kindergarten teacher in Kateman didstrict atotaled of 35 people. Used the sample is saturated sample mean population is sampled.The collection of data technique is used questionnaire. Data analysis and correlationanalysis product moment had tated previously assumptions. The result showed that thereis a relationship between emotional intelligence and classroom management skill. It is ramounted 0,448.Keywords: emotional intelligence, classroom management skill